The gynogenetic reproduction of diploid and triploid hybrid spined loaches (Cobitis: Teleostei), and their ability to establish successful clonal lineages--on the evolution of polyploidy in asexual vertebrates - Janko, Karel; Bohlen, Jörg; Lamatsch, Dunja; Flajshans, Martin; Epplen, Jörg T; Ráb, Petr; Kotlík, Petr; Slechtová, Vera (Genetica, 2007)
Polyploidisation is assumed to have played a significant role in the evolution of hybrid asexual lineages. The virtual absence of natural asexual systems in which more than a single ploidy level successfully establishes successful independent clonal lineages is generally explained by the strong effects of polyploidisation on fitness. Experimental crosses were made between diploid and triploid asexual Cobitis elongatoides x C. taenia hybrids (female) and both parental spined loach species (male). Genotyping of the progeny using allozymes and multilocus DNA fingerprinting, along with flow cytometric measurement of ploidy level, demonstrated the occurrence of gynogenetic reproduction in both female biotypes. The incorporation of the sperm genome occurred in some progeny, giving rise to a higher ploidy level, but the rate of polyploidisation differed significantly between the diploid and triploid females. These outcomes are consistent with the existence of developmental constraints on tetraploidy, which determine the rarity of tetraploids in natural populations. No cases of ploidy level reduction were observed. Since diploid and triploid hybrid populations occur where the lack of potential progenitor excludes the possibility of de novo origin, it is probable that both diploid and triploid females can establish successful clonal lineages. Spined loaches represent a unique example, among asexual vertebrates, where more than one ploidy level can establish persistent clonal lineages, which are reproductively independent of one another.
Keywords: molekulární evoluce; Cypriniformes; Polyploidy; DNA fingerprinting; průtoková cytometrie; diploidie; Reproduction, Asexual; Diploidy; křížení genetické; DNA Fingerprinting; Crosses, Genetic; mužské pohlaví; nepohlavní rozmnožování; Flow Cytometry; Animals; ženské pohlaví; zvířata; Hybridization, Genetic; hybridizace genetická; máloostní; Female; polyploidie; Male; Evolution, Molecular